2019
DOI: 10.3390/ijms21010057
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Equally Stimulate Epithelial Na+ Transport in Male and Female Fetal Alveolar Cells

Abstract: Preterm infants frequently suffer from respiratory distress syndrome (RDS), possibly due to lower expression of epithelial Na+ channels (ENaC). RDS incidence is sex-specific, affecting males almost twice as often. Despite the use of antenatal glucocorticoids (GCs), the sex difference persists. It is still controversial whether both sexes benefit equally from GCs. We previously showed that Na+ transport is higher in female compared with male fetal distal lung epithelial (FDLE) cells. Since GCs increase Na+ tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In retrospective analytic research of a sizable sample of italian neonatal hospitalization data, Condò et al [ 8 ] revealed that birth weight and sex also presented a risk effect on NRDS. The male disadvantage in NRDS was reported by Laube et al [ 9 ] in research of antenatal glucocorticoids stimulation of alveolar cell epithelial Na + transport. However, antenatal glucocorticoids administration had no sex-specific effects on Na + transport, indicating that antenatal glucocorticoids administration had no effect on the male disadvantage in NRDS.…”
Section: Discussionmentioning
confidence: 69%
“…In retrospective analytic research of a sizable sample of italian neonatal hospitalization data, Condò et al [ 8 ] revealed that birth weight and sex also presented a risk effect on NRDS. The male disadvantage in NRDS was reported by Laube et al [ 9 ] in research of antenatal glucocorticoids stimulation of alveolar cell epithelial Na + transport. However, antenatal glucocorticoids administration had no sex-specific effects on Na + transport, indicating that antenatal glucocorticoids administration had no effect on the male disadvantage in NRDS.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, the study suggested that EGF unlikely represents the cause for the sex differences in Na + transport. Furthermore, GCs increased ENaC activity and mRNA expression in FDLE cells, independent of sex and inhibition of GR did not equalize Na + transport between male and female cells, suggesting that GR activity does not contribute to the increased Na + transport in females [106].…”
Section: Alveolar Fluid Clearancementioning
confidence: 89%
“…Their lungs at birth were severely atelectatic and development was impaired at the early canalicular stage [105]. In FDLE cells of fetal rats, GR mRNA expression was significantly higher in female cells, possibly rendering them more receptive to GCs [106]. In contrast, the total number of lung GR and the measured binding affinity did not significantly differ between male and female sheep fetuses [107].…”
Section: Pulmonary Steroid Receptorsmentioning
confidence: 98%
“…In retrospective analytic research of a sizable sample of Italian neonatal hospitalization data, Condò et al [8] revealed that birth weight and sex also presented a risk effect on NRDS. The male disadvantage in NRDS was reported by Laube et al [9] in research of antenatal glucocorticoids stimulation of alveolar cell epithelial Na + transport. However, antenatal glucocorticoids administration had no sex-speci c effects on Na + transport, indicating that antenatal glucocorticoids administration had no effect on the male disadvantage in NRDS.…”
Section: Discussionmentioning
confidence: 99%